2015
DOI: 10.1038/nrclinonc.2015.120
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and challenges of radiotherapy for treating cancer

Abstract: The past 20 years have seen dramatic changes in the delivery of radiation therapy, but the impact of radiobiology on the clinic has been far less substantial. A major consideration in the use of radiotherapy has been on how best to exploit differences between the tumour and host tissue characteristics, which in the past has been achieved empirically by radiation-dose fractionation. New advances are uncovering some of the mechanistic processes that underlie this success story. In this Review, we focus on how th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
341
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 540 publications
(346 citation statements)
references
References 225 publications
(253 reference statements)
2
341
0
3
Order By: Relevance
“…Radiotherapy is a critical component of comprehensive cancer treatment in the developing world (1). It is effective and often curative, but would be more so if radiosensitizers, radioprotectors, and predictive biomarkers of patient and tumor radiation sensitivity were employed (2, 3). Radiation modifiers have been reviewed recently (4-8), as has the potential for radiation therapy to enhance the effectiveness of immunotherapeutics (9-11) to improve local tumor control as well as to induce abscopal effects that result in concomitant responses in distant metastases (12, 13).…”
Section: Introductionmentioning
confidence: 99%
“…Radiotherapy is a critical component of comprehensive cancer treatment in the developing world (1). It is effective and often curative, but would be more so if radiosensitizers, radioprotectors, and predictive biomarkers of patient and tumor radiation sensitivity were employed (2, 3). Radiation modifiers have been reviewed recently (4-8), as has the potential for radiation therapy to enhance the effectiveness of immunotherapeutics (9-11) to improve local tumor control as well as to induce abscopal effects that result in concomitant responses in distant metastases (12, 13).…”
Section: Introductionmentioning
confidence: 99%
“…This is most often observed in combination with immune checkpoint blockade (i.e. anti-CTLA4 antibody) 2224 , suggesting that local radiation can be immunomodulatory. We have extensively characterized how irradiation of one tumor along with immune checkpoint blockade can produce T cell-dependent responses in the contralateral unirradiated tumor using the B16 syngeneic murine model of melanoma 24, 25 .…”
mentioning
confidence: 99%
“…Numerous studies have demonstrated that irradiation can effectively activate the immune system by triggering the release of pro-inflammatory molecules, exposing new tumor antigens through cross-presentation, and upregulating MHC-1 and death receptor expression on tumor cells 29, 30 . Accordingly, tumor-specific immune responses have been shown to develop during the course of radiation therapy in both animal models and humans 31-33 .…”
Section: Sbrt Mechanisms Of Actionmentioning
confidence: 99%